PENGARUH MODEL CRUICKSHANK TERHADAP HASIL BELAJAR MATEMATIKA: THE INFLUENCE OF THE CRUICKSHANK MODEL ON MATHEMATICS LEARNING OUTCOMES - Dewi, Hasma; Ariandini, Nur (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to determine the influence of the cruickshank model on mathematics learning outcomes in grade VIII students of SMP Negeri 1 Marioriawa, Soppeng Regency. This research is an experimental study that uses a quasi-experimental design research design. The study population was all grade VIII students of SMPN 1 Marioriawa, Soppeng Regency for the 2020–2021 school year, a total of 104 people divided into 5 classes. Samples were taken with a simple random sampling technique that was selected into an experimental class taught using the cruickshank model and a control class taught without using the cruickshank model. The research model used is a pretest-posttest control group design. Data collection techniques were carried out using multiple-choice test instruments in the form of 20 numbers. Data analysis techniques are performed with descriptive statistical analysis and inferential statistical analysis. The analysis of inferential data for the instrument was conducted in the form of a test using the Mann-Whitney u-test using SPSS with a significant level of 5%, α = 0.05 previously set. The results of the study showed that there was a significant influence of the cruickshank model on mathematics learning outcomes in grade VIII students of SMPN 1 Marioriawa, Soppeng Regency, where learning outcomes in students taught with the cruickshank model were higher than in students who were taught without applying the cruickshank model.